THE EFFECT OF TRAINING USING RUBBER WEIGHTS AND WITHOUT WEIGHTS ON THE SPEED OF PENCAK SILAT PSHT RANTING CRESCENT KICK TANAH PUTIH TANJUNG MELAWAN - Tika Hariyanti; Aref Vai; Syahriadi (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the effect of training using rubber weights and with-out weights on the speed of the PSHT Tanah Putih Tanjung Melawan pencak silat sickle kick. This study is an experimental study using the True experiment design method. The sample in this study was 14 female athletes. The instrument in this study was a 10-second sickle kick speed test with 3 trials and the best value was taken. Data analysis and testing of the research hypothesis used the t-test analysis technique (t-test) with a significance level of α = 0.05. The results of the study showed that: (1) there was an increase in the speed of the sickle kick after athletes followed a training program using rubber weights with an average value of 13.71 in the pre-test and increased by 6.72 or 7% to 20.43 in the post-test. The statistical results showed that the sig-2 tailed value was 0.000 ≤ 0.05. (2) there is an increase in the speed of the sickle kick after the athlete follows a training program without rubber weights with an average value of 13.43 in the pre-test increasing by 5% to 18.43 in the post-test. With statistical results showing that the sig-2 tailed value is 0.000 ≤ 0.05. (3) there is an increase in kick speed between training using rubber weights and without weights with a sig-2 tailed value of 0.013 ≤ 0.05. It can be concluded that training using rubber weights is more effective in increasing the speed of the sickle kick compared to training without rubber weights in the Pen-cak Silat PSHT Ranting Tanah Putih Tanjung Melawan.